1998
DOI: 10.1152/jappl.1998.85.2.530
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of aerobic endurance running performance in eleven inbred strains of rats

Abstract: The goal of this study was to identify inbred rat strains that could serve as useful models for exploration of the genetic basis of aerobic endurance performance. Six rats of each gender from 11 different inbred strains were tested for 1) maximal running capacity on a treadmill and 2) isolated cardiac performance. Running performance was estimated from 1) duration of the run, 2) distance run, and 3) vertical work performed. Cardiac output, during constant preload and afterload, was taken as a measure of cardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
75
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 88 publications
(82 citation statements)
references
References 18 publications
6
75
1
Order By: Relevance
“…When exhaustion was determined, defined as an inability to maintain running speed despite repeated contact with the electric grid, each mouse was immediately removed from the treadmill and returned to its home cage. Maximal exercise capacity was estimated from each run to exhaustion trial with three parameters: the duration of the run (in min), the distance run (in m), and vertical work performed (in kg ⅐ m) (2,42). In our laboratory, this protocol yields a within-mouse coefficient of variation for work of 10 Ϯ 1% for two tests conducted within 72 h by the same individual (M. P.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…When exhaustion was determined, defined as an inability to maintain running speed despite repeated contact with the electric grid, each mouse was immediately removed from the treadmill and returned to its home cage. Maximal exercise capacity was estimated from each run to exhaustion trial with three parameters: the duration of the run (in min), the distance run (in m), and vertical work performed (in kg ⅐ m) (2,42). In our laboratory, this protocol yields a within-mouse coefficient of variation for work of 10 Ϯ 1% for two tests conducted within 72 h by the same individual (M. P.…”
Section: Animalsmentioning
confidence: 99%
“…Strain-dependent differences in intrinsic or pretraining exercise capacity measured during a graded treadmill test have been reported for inbred mice and rats (2,34,36,62). In a screen of several inbred mouse strains, Lerman et al (34) reported that maximal speed achieved during a graded treadmill test was highest in FVB/NJ (FVB) mice and lowest in C57BL/6J (B6) mice.…”
mentioning
confidence: 99%
“…The treadmill test was stopped when the mouse could not get off the shock grid within 3 s, and exercise endurance was estimated by total time that the mouse ran. This indirect measure of exercise endurance has been used as a phenotype in other rodent genetic studies (1,6,18,26,36), and running speed has been positively correlated with oxygen consumption in mice (13).…”
Section: Estimation Of Exercise Endurancementioning
confidence: 99%
“…6,40 After retrograde perfusion for 15 minutes at 80 mm Hg, anterograde perfusion was initiated at a preload of 15 mm Hg and an afterload of 70 mm Hg for the duration of each study.…”
Section: Isolated Heart Studiesmentioning
confidence: 99%